Analysis of Unemployment Rate and Influencing Factors in East Lombok Regency 2009-2018: Analisis Tingkat Pengangguran dan Faktor-Faktor yang Mempengaruhi Kabupaten Lombok Timur Tahun 2009-2018 - Elfan Hidayat; Prayitno Basuki; Helmy Fuady (Journal of Social and Humanities, 2023)
This study aims to determine the influence of population growth, Gross domestic product (GDP), and inflation on the unemployment rate in East Lombok Regency from 2009 to 2018. This research adopts a quantitative approach with a focus on data analysis using statistical methods. Data collection techniques employed in this study include observation and documentation. The data analysis technique used is multiple regression analysis. The study utilizes data on the unemployment rate, population growth, GDP, and inflation from the Central Statistics Agency of East Lombok Regency and the Central Statistics Agency of West Nusa Tenggara Province during the period of 2009-2018. The results of this study indicate that population growth, GDP, and inflation do not have a significant partial effect on the unemployment rate. Simultaneous testing also reveals that population growth, GDP, and inflation do not have a significant effect on the unemployment rate.